Analisis Implementasi Pendekatan Psikologis pada RPP Mata Pelajaran Al-Qur’an Hadist untuk Meningkatkan Efektivitas Pembelajaran Hadist - Yasmin, Firyal (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
Teaching Al-Qur’an Hadith requires an adaptive approach to create a conducive and effective learning environment. This study aims to analyze the implementation of the Lesson Plan (RPP) using a psychological approach in Al-Qur’an Hadith instruction at MTs Al-Musaddadiyah Garut. Employing a descriptive qualitative research method with a case study design, the study involves teachers and students as the primary subjects. Data were collected through in-depth interviews, observations, and document analysis related to the RPP. The key findings reveal a gap between the planning and implementation of the RPP, influenced by factors such as student motivation and infrastructural limitations. However, the psychological approach has proven effective in enhancing student engagement and learning outcomes, provided it is applied flexibly and according to classroom conditions. This study contributes to the literature by offering new insights into the importance of adapting psychological approaches in the context of Islamic religious education. Nevertheless, this research is limited to one location and a relatively short duration, suggesting the need for further studies with a broader scope to reinforce these findings. The implications of this study include recommendations for the development of more responsive lesson plans that address the psychological needs of students, aiming to improve holistic learning outcomes.